Cross-Sector Collaboration and Public Policy Accountability: Implementation Network of Food Security Policy in Bone Regency - Alwi Alwi; A. Aslinda; Gita Susanti (Indonesian Association for Public Administration (IAPA), 2019)
Public policy accountability is one of the essential concepts in public policy study, as it is a parameter to assess the performance of policymakers and implementers. The primary purpose of this study is 1) to know the performance of the implementation of food security policy; 2) to understand the cross-sector collaboration process as a strategy of public policy accountability. Based on the matching pattern and time series techniques, food policy accountability is still low in Bone Regency. This accountability issue happens because the performance of food policy implementers is still weak, and the cross-sector collaboration process has not been effective. Therefore, the forging agreement, building leadership, building legitimacy, building trust, managing conflict, and planning need to be considered to improve food policy accountability in Bone Regency.